AKTIVITAS INTEGRATED MARKETING COMMUNICATION PT BLUE BIRD TBK DALAM MEMPERKENALKAN APLIKASI MY BLUEBIRD 5 DI MASA PANDEMI COVID-19 - Wulan Muhariani (MASSIVE: Jurnal Ilmu Komunikasi, 2021)
ABSTRACTSomething new from the company, whether it is innovations, policies and the latest achievements from the company, should ideally be communicated and marketed to the public under any circumstances, including during a pandemic. At this time, all companies are challenged to market their products and services, a special strategy is needed to achieve the company's goals. For this reason, this study aims to analyze the implementation of Integrated Marketing Communication (IMC) activities carried out by PT Blue Bird Tbk in introducing the company's latest innovation, namely the My Bluebird 5 application during the COVID-19 pandemic. This research was conducted qualitatively with a case study method and data collection was divided into two, namely primary through interviews and observations; as well as secondary data through literature studies and media coverage results. The conclusion of this research is that PT Blue Bird Tbk has implemented an integrated marketing communication concept to introduce the My Blue Bird 5 application in the midst of a pandemic through various tactics such as from advertising, public relations, internet marketing, sales promotion and direct marketing activities.Keywords: Marketing Communications, Integrated Marketing Communication, Pandemic  ABSTRAKSesuatu yang baru dari perusahaan, entah itu inovasi, kebijakan dan pencapaian terbaru dari perusahaan, idealnya harus dikomunikasikan dan dipasarkan kepada masyarakat dalam kondisi apapun, termasuk di masa pandemi. Pada masa ini, semua perusahaan mendapat tantangan untuk memasarkan produk dan jasanya, dibutuhkan strategi khusus agar tujuan perusahaan tercapai. Untuk itu penelitian ini bertujuan menganalisis penerapan aktivitas Integrated Marketing Communication (IMC) yang dilakukan oleh PT Blue Bird Tbk dalam memperkenalkan inovasi terbaru perusahaan, yaitu aplikasi My Bluebird 5 di masa pandemi COVID-19. Penelitian ini dijalankan secara kualitatif dengan metode studi kasus dan pengumpulan data terbagi menjadi dua yaitu primer melalui wawancara dan observasi; serta data sekunder melalui studi pustaka dan hasil liputan media. Kesimpulan dari penelitian ini adalah PT Blue Bird Tbk telah menerapkan konsep komunikasi pemasasaran terpadu untuk memperkenalkan aplikasi My Bluebird 5 di tengah masa pandemi melalui berbagai macam taktik mulai dari kegiatan periklanan, public relations, pemasaran internet, promosi penjualan dan pemasaran langsung.Kata Kunci: Marketing Communications, Integrated Marketing Communication, Pandemi